Bio-based plant oil polymers and composites - Madbouly, Samy; Zhang, Chaoqun; Kessler, Michael R. (Plastics design library., 2015)
Bio-based Plant Oil Polymers and Composites provides engineers and materials scientists a useful framework to help take advantage of the latest research conducted in this rapidly advancing field-enabling them to develop and commercialize their own products quickly and more successfully. Plant oil is one of the most attractive options as a substitute for non-renewable resources in polymers and composites, and is producing materials with very promising thermomechanical properties relative to traditional, petroleum-based polymers. In addition to critical processing and characterization infor.